2009
DOI: 10.1097/id.0b013e3181b4f98c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platform Switching on Strain Developed Around Implants Supporting Mandibular Overdenture

Abstract: The distribution of the strain developed because of decreasing the abutment size does not favor the use of platform switching in an implant-supported mandibular overdenture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…The most appropriate reduced platform abutment design for securing lesser implant abutment material fatigue is represented by conical emergence abutments with a variable height of 1.5-2mm, freeing extension of the implant platform between 0.5-0.75mm (10). Such platform switching is not advisable in mandibular implant-mucosal support prostheses, since reduction of the diameter of the junction lessens the abutment resistance in response to occlusal loading applied in the posterior area of the overdentures -fundamentally compromising the connecting abutment closest to the area where loading is applied (16).…”
Section: Biomechanical Behaviormentioning
confidence: 99%
“…The most appropriate reduced platform abutment design for securing lesser implant abutment material fatigue is represented by conical emergence abutments with a variable height of 1.5-2mm, freeing extension of the implant platform between 0.5-0.75mm (10). Such platform switching is not advisable in mandibular implant-mucosal support prostheses, since reduction of the diameter of the junction lessens the abutment resistance in response to occlusal loading applied in the posterior area of the overdentures -fundamentally compromising the connecting abutment closest to the area where loading is applied (16).…”
Section: Biomechanical Behaviormentioning
confidence: 99%
“…The type of prosthetic restoration has also been reported to play a role in bone‐level changes after implant placement, but only a single clinical study on platform switching in implant overdentures (IODs) could be identified (Bilhan, Mumcu, Erol, & Kutay, 2010), demonstrating a positive effect of platform switching on ΔIBL. An in vitro study analyzing strain distribution in IODs with non‐splinted abutments did not favor platform switching (Sabet, EL‐Korashy, & El‐Mahrouky, 2009) due to the strain on the surrounding bone of the individual implants. In the present study, the two interforaminal implants were directly splinted with a bar.…”
Section: Discussionmentioning
confidence: 99%
“…13 Bu dizayndaki platform switching modeli, implantdayanak birleşiminin çapının azaltılmasının dayanağın overdentureların posterior bölgesindeki okluzal yüklere karşı direncini azalttığından dolayı mandibuler implantmukozal destekli protezlerde tavsiye edilmemektedir. 19…”
Section: Platformunclassified